Tinjauan Hukum Islam terhadap Uang Panai dalam Perkawinan Adat Bugis - Himas Diningrat; Aggita Harsya Fahrezy; Ilham Jeryawan; Sara Yogi Istiqomah (Syntax Corporation Indonesia, 2024)
This research aims to find out how the marriage process occurs with the tradition of Uang Panai as one of the obligations carried out by the prospective groom. This research uses secondary research methods, namely taking data based on manuscripts or published data, making it easier to research and the accuracy of the information. If a man wants to get married to a prospective bride, in Bugis tribal custom there are several considerations that must be prepared, including the nominal value of the panai money which varies and makes it controversial for the community. Basically panai money is different from dowry money. In the view of Islamic law, the best dowry is the dowry that makes things easier for the prospective groom. Easy doesn't always mean easy and little. The reality that occurs in the panai money custom actually intersects with Islamic law. Because the reality is that the nominal amount requested in panai money actually creates more suffering for prospective grooms who want to carry out a wedding but are held back by the nominal amount requested by the prospective female's family.